Recent advances in the methanol synthesis via methane reforming processes - Usman, M.; Daud, W.M.A.W. (Royal Society of Chemistry, 2015)
Depleting fossil fuel resources and continuously degrading environment due to greenhouse gases demands an immediate search for alternative energy resources on an emergency basis to develop a sustainable and green environment. The utilization of coke oven gas, biogas and flue gases from fossil fuel power plants to produce synthesis gas, which is a major feedstock for the production of liquid fuels (methanol), is beneficial both from economical and environmental aspect. In this review paper, our aim is to discuss the applicability of these sources in different reforming processes to produce suitable syn-gas ratio (∼2) for methanol production. The feasibility, suitability and applicability of each source have been discussed in detail accompanied with their environmental impact and detailed economic analysis. Moreover, the influence of different supports, promoters and preparation methods on the catalyst properties to minimize carbon deposition has also been described. This review will summarize all the recent advances in the area of syn-gas production for methanol synthesis.